Modeling and Simulation of Voltage Inverter fed Induction Motor with Stator flux orientation - Goran Rafajlovski, Emil Ratz, Dionis Manov, Slobodan Mircevski: (IEEE-IAS Annual Meeting, Orlando, Florida USA 1995, Vol.1,pp 546-552, 1995)
This paper deals with the application of a nonlinear control technique in a three phase inverter-fed induction motor. Also, a mathematical model for the dynamic analysis of an induction motor and voltage controlled inverter in a stator co-ordinate system is described. Digital simulation has been utilised to prove the performance and simplicity of the induction motor mathematical formulation. This model can be easily transformed for a freely chosen rotating frame of reference. In this control system for a stator flux controlled induction motor, the instantaneous values of the flux and torque are calculated from only the primary current variables. By using instantaneous voltage space vectors, with the selection of optimum inverter switching modes employing vector modulation technique, direct control of torque and stator flux is achieved.
Keywords: Modelling, Simulation, Voltage Inverter, Induction motor, Stator Flux